The price system and resource allocation - Leftwich, Richard H. (New York : Holt, Rinehart and Winston, 1960)
The intent in this revision has been to improve the analysis and its exposition at various points throughout the book. The basic purposes, frame of reference, coverage, emphasis, and method of exposition are as they were in the first edition
Includes bibliographical references and index.
uaa 21/01/2019
Loans
Keywords: Prices; Pricing; Microeconomics